Legal Opportunities of Bank Interests: Reinventing Analysis of the Mashlahat Theory of Al-Syathibi - Anwar Sadat (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This study described the analysis of legal opportunities in a bank saving interest. In general, banks in Indonesia are very influential on the dynamics of the economic life of society. Existence evenly spread to remote. This has implications on the ease of access and services to the wider community. If the determination of the bank savings raised interest prohibition, can lead to economic turmoil in the form of a massive diversion of funds by customers that can systemically affect the stability of national economy. Considering the majority of government agencies (including ministries of religion) and private sectors to accommodate the livelihood of the general public, especially civil servants and private employees, which is increasingly dependent on the existence of a conventional bank. Mashlahat theory put forward by al-Syatibi can provide legal opportunities, both macro (general) and micro (personal). In this study, the author find that there are legal opportunities of bank savings interest in the analysis al-Syatibi's theory of Mashlahat